Locating African European studies
1 online resource.
Keywords: Drawing on a rich lineage of anti-discriminatory scholarship, art, and activism, Locating African European Studies engages with contemporary and historical African European formations, positionalities, politics, and cultural productions in Europe. Locating African European Studies reflects on the meanings, objectives, and contours of this field. Twenty-six activists, academics, and artists cover a wide range of topics, engaging with processes of affiliation, discrimination, and resistance. They negotiate the methodological foundations of the field, explore different meanings and politics of African' and European', and investigate African European representations in literature, film, photography, art, and other media. In three thematic sections, the book focusses on: African European social and historical formations African European cultural production Decolonial academic practice Locating African European Studies features innovative transdisciplinary research, and will be of interest to students and scholars of various fields, including Black Studies, Critical Whiteness Studies, African American Studies, Diaspora Studies, Postcolonial Studies, African Studies, History, and Social Sciences.